(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Over the past few decades, the Kirkuk region in Iraq has been seriously threatened by global warming under climate and temperature change scenarios. Over the course of a year, the study examines the spatio-temporal fluctuations in Land Surface Temperature (LST) and how they affect the vegetation cover in Kirkuk, Iraq for the period from January 1, 2019, to December 31, 2019. Utilizing satellite data and Geographic Information Systems (GIS) techniques, the study analyzed the correlation between LST and the Normalized Difference Vegetation Index (NDVI) showing a fair but negative correlation (R² = 0.65). Additionally, the relationship between NDVI and Kirkuk wheat yield indicated a strong positive correlation (R² = 0.89). The results reveal that the factors such as urban expansion, changes in cropping patterns and global climate change contributes to the increase in LST. The findings highlight the importance of using remote sensing and GIS tools to assess climatic influences on environmental conditions, which are essential for sustainable land management and agricultural practices in the context of global climate change.